Omrežja, otočja in puščave samoorganizirane prehranske oskrbe - Struc, Nežka (Svetovi (Ljubljana), 2025)
The article discusses the importance of self-organised networks for local food supply in Maribor as a key factor in preventing food deserts. Their practices represent “islands” or networks of solidarity economies that create space for the distribution of locally produced food. By having direct contact with consumers, producers avoid instability and are less exposed to the influence of large commercial chains, which also partially addresses the issue of surplus production. Such networks may initially seem closed off, distant and isolated from mainstream food distribution, but in fact they strengthen rural-urban partnerships.
Keywords: anthropolog y of networks; antropologija omrežij; food deserts; food networks; food supply; local community; lokalna skupnost; Maribor; prehranska omrežja; prehranska oskrba; prehranske puščave; samoorganizirana omrežja; self-organised networks; Slovenia; Slovenija; solidarity; solidarity economy; solidarnost; solidarnostna ekonomija; sustainable food supply; trajnostna oskrba; urban anthropology; urbana antropologija